Advances in FUZZY techniques and applications: in occasion of Lotfi Zadeh 100 birth anniversary - Xu, Zeshui; Herrera-Viedma, Enrique (Technological and Economic Development of Economy, 2021)
Advances in FUZZY techniques and applications: in occasion of Lotfi Zadeh 100 birth anniversary. Technological and Economic Development of Economy, 27(2), pp. 280-283.